2022
DOI: 10.3389/fams.2022.808489
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of COVID-19 Pandemic on Dollar Exchange Rate of Pakistan

Abstract: The Coronavirus disease (COVID-19) most likely began in an animal species and subsequently transmitted to humans in Wuhan, China, a city of 11 million people, on December 29, 2019, when the first case was recorded. The Coronavirus then transmitted from person to person by infected droplets from a sick person's coughing, sneezing, or contaminated hands. Hence, the purpose of the study is to see the impact of the outbreak of COVID-19 daily tests on the Pakistani rupee against the US dollar exchange rate using Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Engebretsen and Anderson [29] found that the countries who are net oil exporters are facing a historic double blow: a worldwide economic slowdown brought on by the COVID-19 pandemic and an oil market meltdown, with the benchmark price for US crude oil, the West Texas Intermediate, briefly falling below zero for the first time in history (in April 2020). The authors [8,[30][31][32][33][34] did the most similar work as like our study. The International Energy Agency forecasts that oil and gas revenues for several significant producers will fall by 50% to 85 % in 2020, compared to 2019, based on an oil price of USD 30 per barrel, although the losses could be more significant depending on the future market development.…”
Section: Literature Reviewsupporting
confidence: 58%
“…Engebretsen and Anderson [29] found that the countries who are net oil exporters are facing a historic double blow: a worldwide economic slowdown brought on by the COVID-19 pandemic and an oil market meltdown, with the benchmark price for US crude oil, the West Texas Intermediate, briefly falling below zero for the first time in history (in April 2020). The authors [8,[30][31][32][33][34] did the most similar work as like our study. The International Energy Agency forecasts that oil and gas revenues for several significant producers will fall by 50% to 85 % in 2020, compared to 2019, based on an oil price of USD 30 per barrel, although the losses could be more significant depending on the future market development.…”
Section: Literature Reviewsupporting
confidence: 58%
“…To model the effect that the COVID-19 pandemic may have on the exchange rate of the Moroccan Dirham against the Euro currency, the VAR model seems to be the best approach to monitor and study such a causal interaction. The analysis of the shocks caused by COVID-19 on the exchange rate and the evaluation of the causal link between the two variables are done with the help of structural analysis, which includes the methods of causality in the sense of Granger, impulse response function and variance decomposition of the prediction errors [9].…”
Section: European Union Currency (Madeur) the Model Used Is The Vecto...mentioning
confidence: 99%